PENGARUH PENYIRIH TERHADAP PLAK DAN CALCULUS PADA ANAK UMUR 10-12 TAHUN DI DESA BATU KARANG KECAMATAN PAYUNG KABUPATEN KARO - Kartika Emailijati; , Nurhamidah; Ni Ketut Nuratni (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2022)
Oral health is important for general health and well-being and greatly affects the quality of life. Oral health problems will have an impact on a person's performance. The problem of high rates of dental and oral disease at this time is strongly influenced by several factors, including community behavior factors that are used as a culture or habit, one of which is the habit of chewing betel or areca nut (Nurjannah et al, 2010). According to Boediharjo (1988) plaque and calculus are also the main causes of periodontal disease. This disease can attack us at all ages, both in children and adults . This research is an analytic quantitative research with Case Control design with a simple linear regression analysis test, partially test the hypothesis (t test) and test the hypothesis Simultaneously (Test f). The population of all children aged 10-12 years is 150 people with samples, 30 were betel nut and 30 were not, the results obtained in this study were plaque statuson betel nut in the bad category (63.4%) and calculus status in the bad category (53.4%).